2019
DOI: 10.1007/s42250-019-00112-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CaO–Ag-NPs @CaCO3 Nanocomposite via Impregnation of Aqueous Sol Ag-NPs onto Calcined Calcium Oxalate

Abstract: In this research CaO-Ag-NPs @CaCO 3 nanocomposite was prepared by treatment of calcined calcium oxalate [CaO, Ca(OH) 2 and CaCO 3 ] with sol of silver nanoparticles (Ag-NPs). Several techniques were used to investigate the structural properties of CaO-Ag-NPs@CaCO 3 nanocomposite including FTIR, UV/VIS, XRD, TEM and TGA. XRD and TEM and UV/VIS results showed that silver nanoparticles incorporated with calcium oxide (CaO-Ag-NPs) are incorporated with calcium carbonate (CaO-Ag-NPs@CaCO 3). It is confirmed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The particle size observed using TEM corresponds well with the average crystallite size estimated by Xray diffraction (XRD). This finding aligns with the results reported by (22).…”
Section: High-resolution Transmission Electron Microscopy (Hrtem)supporting
confidence: 94%
“…The particle size observed using TEM corresponds well with the average crystallite size estimated by Xray diffraction (XRD). This finding aligns with the results reported by (22).…”
Section: High-resolution Transmission Electron Microscopy (Hrtem)supporting
confidence: 94%
“…00-004-0777, it demonstrated a cubic structure without impurities. 20 , 27 , 44 , 45 In the XRD pattern of CaO, a few low-intensity calcite peaks (CaCO 3 ) illustrate rapid carbonation of CaO by atmospheric CO 2. 46 Upon codoping, the slightly shifted layer spacing to higher values is attributed to the homogeneous distribution of Ce and CNC between interlayers of pure CaO, which is consistent with the peak shift observed in XRD spectra.…”
Section: Resultsmentioning
confidence: 99%
“…25 A recent study reported that a CaO-Ag-NPs@CaCO 3 nanocomposite showed strong antimicrobial activity against Escherichia coli and Staphylococcus aureus. 26 It is also used as an absorbent, water soener, and potential hydrogen regulator for wastewater and in fertilizers. 27 The properties of multi-metal composite oxides fabricated from the assembly of individual oxides make the materials potentially signicant in the elds of electronic devices, catalysis, photocatalysis and nonlinear optical and semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%